Sustainable transportation system in Universiti Putra Malaysia: perspectives from university students and academic staffs - Sabri, Bukryman; Phua, Chai Han (Malaysian Consumer and Family Economics Association, 2021)
The implementation of the Sustainable Transportation System by the university management in Universiti Putra Malaysia (UPM) as part of the University Green Policy is to lessen the usage of any private vehicles entering the campus area every day. The main purpose of this study is to determine whether Sustainable Transportation System is effective to be implemented in Universiti Putra Malaysia (UPM). One hundred eleven respondents participated in this study, mainly of first and final year students, postgraduate students, lecturers, academic staff, and administrative and supporting staff randomly selected through the convenience sampling method. The data has been generally collected through the questionnaire method. The findings had shown that nearly 67 per cent of the respondents are using private transportation mode to travel into the campus area daily. The findings also show that Sustainable Transportation System is not practical to be implemented in Universiti Putra Malaysia (UPM) (r = -.072, p = .455). Then, there are no significant differences between any type of transportation mode usage towards implementing the Sustainable Transportation System in Universiti Putra Malaysia (UPM) (t = .717, p = .399). However, a correlation occurred between the perceptions and attitudes among the university students and academic staff towards the effectiveness of implementing the Sustainable Transportation System in Universiti Putra Malaysia (UPM) (r = .273, p = .004). Thus, all university students and academic staff need to change their perceptions and attitude to using any public transportation services. The university management also must carry out more effective approaches to ensure implementing a Sustainable Transportation System. A future research study can be expanded into larger sample sizes such as streamers and international students besides further identifying the knowledge level and the perceptions and attitudes among the respondents towards Sustainable Transportation System in the UPM campus.